Pengembangan Permainan Edukatif Ragam Budaya Nusantara Berbasis Android - Dony Defrianto; Rinta Kridalukmana; Ike Pertiwi Windasari (Jurnal Teknologi dan Sistem Komputer, 2015)
This research aims to develop a game software that can be used as an alternative means of learning media in Indonesian local culture for the community in the form of the game in the Android operating system. The methodology used in this study is the Multimedia Development Life Cycle (MDLC) sourced from Luther and has been modified by Sutopo, which consists of six stages, namely the concept, design, collection of material, manufacture, testing, and distribution. Testing applications that have been created using black-box method, which is carried out to check the functions contained in the application. The process of application testing is done by using a questionnaire. The testing is done objectively by asking ratings from users of the application. Therefore, the results of the study that were obtained using black-box method, indicates that the game is already working according to specifications needed to show test results for each application functions and buttons. And the results of the questionnaire data obtained by the average score of all ratings amounted to 84%. And it can be concluded that the applications made are well-qualified.